2017
DOI: 10.1016/j.gaitpost.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hip joint centre mislocation on gait kinematics of children with cerebral palsy calculated using patient-specific direct and inverse kinematic models

Abstract: Joint kinematics can be calculated by Direct Kinematics (DK), which is used in most clinical gait laboratories, or Inverse Kinematics (IK), which is mainly used for musculoskeletal research. In both approaches, joint centre locations are required to compute joint angles. The hip joint centre (HJC) in DK models can be estimated using predictive or functional methods, while in IK models can be obtained by scaling generic models. The aim of the current study was to systematically investigate the impact of HJC loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…One investigator (JB) placed 12 surface markers (14mm diameter) on anatomical landmarks of the pelvis and lower limbs (Kainz et al, 2017a). Additionally, a cluster of four markers was strapped to each thigh and shank (Lerner et al, 2014).…”
Section: Motion Capture Experimentsmentioning
confidence: 99%
“…One investigator (JB) placed 12 surface markers (14mm diameter) on anatomical landmarks of the pelvis and lower limbs (Kainz et al, 2017a). Additionally, a cluster of four markers was strapped to each thigh and shank (Lerner et al, 2014).…”
Section: Motion Capture Experimentsmentioning
confidence: 99%
“…However, where the deformity remains the same across the different sessions, hip internal-external rotation reproducibility should remain constant even if the crosstalk correction is affected. Moreover, as the geometrical method is exclusively based on joint centre location, it might be sensitive to errors on joint centres, as has been reported for the hip [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…While it is expected that soft-tissue artifact increases with excess tissue [47] and high-impact activities, constrained-kinematic models appear to be well suited to minimize such effects. Joint kinematics are sensitive to joint-axis location and orientation [48,49], which may be affected when scaling generic musculoskeletal models to subject-specific anthropometry. To mitigate these potential errors, we visually confirmed that each subject-specific model closely matched the neutrally-aligned position.…”
Section: Discussionmentioning
confidence: 99%